Epinephrine in the tumescent technique for hypospadia surgery (Faculty of Medicine Universitas Indonesia, 2012)
The use of tumescent technique, which contains epinephrine, in penile surgery has not been reported previously. Two patients with hypospadias had reconstructive operation using tumescent technique with a